OS SABERES DOCENTES DE PROFESSORES GRADUADOS EM CIÊNCIAS BIOLÓGICAS: UM ESTUDO COM PROFESSORES INICIANTES. - LARA CASSIANO PEDREIRA LOPO (2023)
This research aimed to identify which and how the teaching knowledge of Science and Biology teachers at the beginning of their careers is constructed. It is known that the professional development of teachers is a continuous process that adds knowledge, experiences, attitudes, concepts and practices throughout the teaching career. In an initial period, there is a process of transition from the status of student to professional teacher, in which there is an intensification of professional and personal learning. In addition, different researchers in Brazil and around the world claim that teaching knowledge is plural, constituted through different experiences, whether personal, formative or professional. That said, this study used a quali-quantitative approach, through the application of a questionnaire and semi-structured interview as methodological procedures. Initially, a questionnaire was applied to 17 Science and Biology teachers from the state and municipal public network in the cities of Corumbá and Ladário-MS and, based on these initial results, 4 teachers, beginners in the teaching career, were selected for an interview, aiming to deepen the theme of teaching knowledge in beginning teachers. For interpretation and analysis of the information obtained from the questionnaires, descriptive statistics and frequency of responses were used, which helped the qualitative discussions. The interviews were analyzed using Content Analysis. The results indicate that the participating teachers consider pedagogical knowledge and experiential knowledge to be important for starting their careers. Beginning teachers use the knowledge learned during graduation as a basis for their practice, but they improve this knowledge during the exercise of the profession, as they do not feel, when entering a classroom, fully prepared for the different situations they encounter in their daily lives. It is hoped that this work will help beginner teachers understand the development of teaching knowledge in the early years of their careers and, with this, it seeks to contribute to the initial and continuing training of teachers. Moreover, having an understanding of how this knowledge is constituted, teachers in practice can perform their profession with more awareness and competence.